2008
DOI: 10.1287/orsc.1070.0264
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Flows Within Multinational Corporations: Explaining Subsidiary Isolation and Its Performance Implications

Abstract: Applying a new theoretical and empirical approach to intrafirm knowledge transfers, this paper provides some initial insight to the little-researched phenomenon of why some subsidiaries are isolated from knowledge-transfer activities within the multinational corporation (MNC). Knowledge transfer is framed as a problemistic search process initiated by the recipient unit. We show that knowledge flows from units that are perceived to be highly capable to units that perceive themselves to be highly capable. Knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
295
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(312 citation statements)
references
References 80 publications
11
295
0
6
Order By: Relevance
“…These nonroutine problems are triggered by current or anticipated changes in the environment and cause a behavioral response in the form of solution searching which is aimed at closing this mismatch between current organizational processes, practices and competences and the changing requirements in the marketplace. This motivated search behavior may lead to relevant knowledge to be sought and selected (Schulz, 2003), and has been previously linked to MNC knowledge flows (Monteiro, Arvidsson, & Birkinshaw, 2008;Zellmer-Bruhn, 2003), as it leads to subsidiary knowledge inflows if knowledge is mobilized from other MNC units to assist the subsidiary-level solution finding activities.…”
Section: Knowledge Inflows As Outcome Of Knowledge Mobilizations Drivmentioning
confidence: 99%
See 1 more Smart Citation
“…These nonroutine problems are triggered by current or anticipated changes in the environment and cause a behavioral response in the form of solution searching which is aimed at closing this mismatch between current organizational processes, practices and competences and the changing requirements in the marketplace. This motivated search behavior may lead to relevant knowledge to be sought and selected (Schulz, 2003), and has been previously linked to MNC knowledge flows (Monteiro, Arvidsson, & Birkinshaw, 2008;Zellmer-Bruhn, 2003), as it leads to subsidiary knowledge inflows if knowledge is mobilized from other MNC units to assist the subsidiary-level solution finding activities.…”
Section: Knowledge Inflows As Outcome Of Knowledge Mobilizations Drivmentioning
confidence: 99%
“…Ambos & Ambos, 2009;Björkman, Barner-Rasmussen, & Li, 2004;Driffield, Love, & Menghinello, 2010;Gupta & Govindarajan, 2000;Monteiro et al, 2008;Schulz, 2001Schulz, , 2003Tsai, 2001Tsai, , 2002, or analyzed patent citations (Kotabe et al, 2007), investigating problemistic search in response to particular challenges allows developing a more nuanced view of how knowledge inflows that may appear in these summary measures are actually initiated in practice.…”
Section: Mnc Knowledge Flows At the Individual-level: The Central Rolmentioning
confidence: 99%
“…As Birkinshaw and Hood (1998) note, the effective transfer of capabilities from one location to another is hampered by impediments to acquisition of internal resources. This scenario might lead certain subsidiaries to become "isolated" from the MNC's knowledge-creation activities (Monteiro et al, 2008). Bouquet and Birkinshaw (2008) also document how subsidiaries gain attention from the headquarters using subsidiary level constructs such as 'weight' (structural positions that subsidiaries occupy within the multinational firm) and 'voice' (initiative taking).…”
Section: Contributionsmentioning
confidence: 99%
“…Local subsidiaries are in a position to tap local knowledge reservoirs, acquire business critical information, and transfer it back to their headquarters (e.g. Monteiro et al, 2008). Previous studies have also found a strong link between marketing specific knowledge management, and firm performance (Wang et al, 2009), but reverse knowledge transfer (RKT) has proven to be a difficult process.…”
Section: Introductionmentioning
confidence: 99%
“…This paper contributes to the existing literature on RKT by concentrating to the increasingly important EM context from the point of view of marketing. The lack of studies in international marketing literature addressing the topic is acknowledged (Monteiro et al, 2008), although EM subsidiaries increasingly hold a key role in the global strategy of MNEs. Scholars have also stressed that very few attempts have been made to explain the reasons for success or failure of reverse knowledge flow from subsidiaries located in EMs (Ambos & Ambos, 2009;Bouquet & Birkinshaw, 2008).…”
Section: Introductionmentioning
confidence: 99%